Fabrication of inverse opal photonic gel sensors on flexible substrates by transfer process. Issue 15 (22nd June 2021) - Yoon, Sohee; Park, Habeen; Lee, Wonmok
Abstract : Sequential transfers of two photonic gels on a flexible substrate enabled the fabrication of dual sensors on a chip. Abstract : We demonstrate a platform technology for transferring opal films and photonic gel films to flexible substrates. The conventional fabrication procedure for inverse opal photonic gel (IOPG) sensors comprises three major steps: 1) the self-assembly of polystyrene μ-spheres to an opal template film within a channel between the top and bottom substrates, 2) infiltration and photo-polymerisation of the monomer mixture, and 3) etching of the opal template. Owing to the low processing yield of the first step, it is difficult to fabricate multiple sensor arrays on a single substrate. In this study, an opal film is formed between two substrates with different surface polarities, and the film is separated by disassembling the two substrates. The opal film on a medium polar substrate is covered using a flexible polyethylene terephthalate (PET) film, and opal-templated photo-polymerisation is performed. Finally, the photonic gel with the opal template is transferred to the PET film, and the opal template is etched out. Using the platform technique, the fabrications of pH-responsive IOPG and temperature-responsive IOPG sensors on PET films are respectively demonstrated. In addition, the IOPG containing the copolymer of acrylamide and 3-acrylamidophenylboronic acid was found to be responsive to glucose at physiological pH. All three sensors were fabricated using the same transfer method, differing only in the composition of monomer mixtures, and they all showed excellent sensitivity and repeatability on PET substrates. Due to the advantageous feature of the transfer method, dual sensors of pH-responsive IOPG and temperature-responsive IOPG were sequentially fabricated on a single PET film.